Anomalies in SU(4) Grassmannian Model - Jusak S Kosasih (Institut Teknologi Bandung, 2003)
The anomalies of the SU(4) Grassmannian model will be considered following the standard model analysis of anomalies. We will consider the Adler-Bardeen anomaly of the U(1) axial current and also its cancellation in the standard model. We also give a quick review on the gravitational as well as SU(2) anomalies in the standard model. In order to give a concrete and explicit example of anomaly calculation, we will use matter representation of SU(4) Grassmannian model. It will be shown that the SU(4) Grassmannian model is free from anomaly.